Researches for the determination of seed material viability of Asteraceae family representatives stored in the Seed bank of the natural flora of Kazakhstan - Махмудова, К.Х.; Мурзатаева, Т.Ш.; Ситпаева, Г.Т.; Елубаева, А.С.; Муган, А.; Дүкенбаева, Б.С.; Саржанова, С.Д. (Fundamental and Experimental Biology, 2023)
We present to your attention the beginning of a series of scientific and educational articles describing the results of research conducted in the laboratory “Seed Bank” of the RSE “Institute of Botany and Phytointroduction”. This series of articles is also aimed at attracting interest and attention to the work of the Seed bank. Current article presents studies of representatives of the Asteraceae family stored in the Seed bank of the Natural flora of Kazakhstan (hereinafter SB). Methods used in SB operation are described: conditions of seed material storage, determination of seed viability. Information on conditional division of stored samples into medicinal, ornamental and endemic species is given. Data on the results of determining the germination rate of seeds of representatives of the Asteraceae family are also presented.